2019
DOI: 10.1371/journal.ppat.1007877
|View full text |Cite
|
Sign up to set email alerts
|

The YIN and YANG of lipoproteins in developing and preventing infectious arthritis by Staphylococcus aureus

Abstract: Rapid bone destruction often leads to permanent joint dysfunction in patients with septic arthritis, which is mainly caused by Staphylococcus aureus ( S . aureus ). Staphylococcal cell wall components are known to induce joint inflammation and bone destruction. Here, we show that a single intra-articular injection of S . aureus lipoproteins (Lpps) into mouse knee joints induced chronic destructive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
85
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(89 citation statements)
references
References 51 publications
2
85
2
Order By: Relevance
“…In contrast to neutrophils, monocytes/macrophages play a vital role in the pathogenesis of S. aureus septic arthritis by aggravating the severity of arthritis in mice 32 . Indeed, the progression of septic arthritis was strongly mediated by monocytes/macrophages through TLR2, but not by neutrophils, in staphylococcal Lpp-induced knee joint arthritis 6 . Chemokines, such as neutrophil chemoattractants KC and MIP-2, are crucial recruiters of neutrophils 33 .…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…In contrast to neutrophils, monocytes/macrophages play a vital role in the pathogenesis of S. aureus septic arthritis by aggravating the severity of arthritis in mice 32 . Indeed, the progression of septic arthritis was strongly mediated by monocytes/macrophages through TLR2, but not by neutrophils, in staphylococcal Lpp-induced knee joint arthritis 6 . Chemokines, such as neutrophil chemoattractants KC and MIP-2, are crucial recruiters of neutrophils 33 .…”
Section: Discussionmentioning
confidence: 95%
“…Chemokines, such as neutrophil chemoattractants KC and MIP-2, are crucial recruiters of neutrophils 33 . Previous studies demonstrated the rapid release of KC in murine peritoneal macrophages upon stimulation by purified staphylococcal Lpp through TLR2 6 . This is in line with our current hematogenous staphylococcal septic arthritis study; Lpp triggered the systemic release of KC to a significantly higher extent than those of the lgt-deficient mutant strain, possibly mediated via TLR2.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…For example, lgt and lsp deletion derivatives of Streptococcus equi (Hamilton et al, 2006) and Streptococcus suis (De Greeff et al, 2003), did not display attenuation in their natural hosts (pony and pig, respectively). Moreover, although a Listeria monocytogenes lgt mutant fails to activate TLR2 signaling it is significantly less virulent in a mouse infection model (Machata et al, 2008), whereas lgt mutants of Streptococcus agalactiae (Henneke et al, 2008) and Staphylococcus aureus (Bubeck Wardenburg et al, 2006;Mohammad et al, 2019) are hypervirulent in mouse infection models. These results imply a subtle and strain-specific balance between escaping protective immune defense related to loss of TLR2 activation and attenuated virulence by the loss of lipoprotein acylation in lgt mutants.…”
Section: Discussionmentioning
confidence: 99%